Establishing a Relationship between Uterine Myoma and Thyroid Nodules Using Medical Ultrasonographic Pattern Approach - Clottey, S. K. (University of Ghana, 2014)
Background: Every cell in the body depends on the thyroid hormones for regulation of their metabolism. About 5-10% of thyroid nodules are suggested to be malignant. Many philosophies explain myoma growth through different pathways and most make mention of estrogen as a contributor. Estrogen is known to have influence on thyroid function, and suspected to have a role in formation of thyroid nodules. Estrogen receptors have been found in normal and neoplastic thyroid tissue and have increased numbers in uterine myoma compared to the normal myometrium. Does estrogen implication imply both thyroid nodule and uterine myoma simultaneously exist in women? Aim: The aim of this research work was to test for relationship between uterine myoma and thyroid nodule among women using medical ultrasonographic approach. Methods: Adult females (n=326) were ultrasonographically screened for the presence of thyroid nodules and uterine myoma using a cross sectional study and a convenient sampling method. The sonographic imaging was done using Toshiba Nemio XG ultrasound equipment with linear probe (7.0-11.0) MHz and convex probe (3.5-5.0 MHz). Blood groups (A, B, O and Rh) were tested after 5mls of blood was drawn from each participant, using blood grouping antigen screening serum. Results: The relationship between uterine myoma and thyroid nodule was significant (p=0.0005) at 95% confidence interval among the participants using Chi-square. The ratio of participants with myoma and thyroid nodule (myo+/thy+) to myoma without (myo+/thy-) was approximately 2:1 (23.31% to 11.65 %). Comparatively, blood group A (44%) and B (57%), were more prone to present with myoma and thyroid nodule respectively among the study population.
Thesis (MSc) - University of Ghana, 2014